2012
DOI: 10.1002/ccd.24360
|View full text |Cite
|
Sign up to set email alerts
|

Impact of radial‐to‐aorta vascular anatomical variants on risk of failure in trans‐radial coronary procedures

Abstract: Failure of trans-radial procedures is associated to anatomic variants located from the wrist to the aorta. The "operative" ABC classification of anatomic variants is useful not only to categorize these anatomic variants, but also to predict the risk of failure of trans-radial approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…This was a retrospective study including all consecutive TRA STEMI patients in our center during this period and considering our center as a highly experienced radial center with 99% of wrist angiographies, we had lower rate of TRA failure with 3% compared to other published studies [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a retrospective study including all consecutive TRA STEMI patients in our center during this period and considering our center as a highly experienced radial center with 99% of wrist angiographies, we had lower rate of TRA failure with 3% compared to other published studies [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The reported overall failure in transradial procedures is between 1% and 10% [15][16][17][18][19]. Prior studies have reported that arterial anomalies found from wrist to aorta influence the success of transradial access and are cause for access crossover from TRA to other access sites [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, anatomical arterial anomalies of the radial course and brachiocephalic system may hinder catheterisation while aortic arch variants often force operators to abandon the radial approach [4,9].…”
Section: Discussionmentioning
confidence: 99%
“…18 Despite these promising reports, the use of "secondary" radial approach did not enter the routine practice of many centers. The need to deal with upper arm vascular anatomic variants 19 • adopting the ulnar artery when bilateral abnormal radial anatomy was known or suspected on the bases of previous procedures.…”
Section: Bleedings and Vascular Complicationsmentioning
confidence: 99%